PRINCIPALS AS MANAGERS OF PRIMARY AND SECONDARY SCHOOLS: STATE OF THE ART OF QUALITATIVE RESEARCH - KONVALINKA, Michal (Trends in education, 2017)
The purpose of this literature review is to bring up the state of the art of qualitative research in this subject. This article is focused on the field of management in primary and secondary schools from the point of view of headteachers as managers of these educational institutions. The results highlight the vital aspects of the discussion. The work is relevant to researchers devoted to school management, and also to directors who would like to find relevant articles on this topic. The main method used to identify relevant articles was a systematic review based on specific keywords. Searches were made in the Web of Science and Scopus databases. The default keywords were: headteacher, school, principal, qualitative, interview, case study, focus group, and mixed methods. The work attempts to capture, in particular, all the important academic papers which consider directors as their main subjects of exploration. The work is focused on qualitative research and includes both foreign and Czech papers.
Keywords: literature review; headteacher; school; principal; qualitative research